2014
DOI: 10.1016/j.cell.2013.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing Protective Tumor Microenvironments to Antibody-Mediated Therapy

Abstract: Therapy-resistant microenvironments represent a major barrier towards effective elimination of disseminated malignancies. Here, we show that select microenvironments can underlie resistance to antibody-based therapy. Using a humanized model of treatment-refractory B-cell leukemia, we find that infiltration of leukemia cells into the bone marrow rewires the tumor microenvironment to inhibit engulfment of antibody-targeted tumor cells. Resistance to macrophage-mediated killing can be overcome by combination regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 36 publications
4
160
0
1
Order By: Relevance
“…Furthermore, M2-skewed macrophages showed increased in vitro phagocytic capacity of rituximab-opsonized chronic lymphocytic leukemia cells in contrast with M1 macrophages, suggesting that CD163 is a rational marker to identify TAM that participate in rituximab-mediated antitumor responses. 85 However, it is notable that the recent study by Pallasch et al 86 reported that antitumor responses to an anti-CD20 antibody were achieved in the macrophage-rich environment in the spleen, but not in the macrophage-poor bone marrow. Fig.…”
Section: M2 Polarization Of Macrophagesmentioning
confidence: 88%
“…Furthermore, M2-skewed macrophages showed increased in vitro phagocytic capacity of rituximab-opsonized chronic lymphocytic leukemia cells in contrast with M1 macrophages, suggesting that CD163 is a rational marker to identify TAM that participate in rituximab-mediated antitumor responses. 85 However, it is notable that the recent study by Pallasch et al 86 reported that antitumor responses to an anti-CD20 antibody were achieved in the macrophage-rich environment in the spleen, but not in the macrophage-poor bone marrow. Fig.…”
Section: M2 Polarization Of Macrophagesmentioning
confidence: 88%
“…103 Preclinical and translational advances. Within the abundant preclinical literature that has been published during the last 13 months on ICD-inducing chemotherapeutics, we found of particular interest the works of: (1) Pallasch and colleagues (Massachusetts Institute of Technology; Cambridge, MA, US), who demonstrated that cyclophosphamide induces an acute secretory phenotype in malignant cells, stimulating the release of various immunostimulatory cytokines that promotes a macrophagedriven, tumor-targeting innate immune response; [104][105][106] (2) Tavora and collaborators (Barts Cancer Institute; London, UK), who showed that the inhibition of protein tyrosine kinase 2 (PTK2, also known as FAK) [107][108][109] in the endothelial tumor [130][131][132][133] in the establishment of a collagenenriched tumor microenvironment contributing to the resistance of (at least a subset of) breast carcinomas to doxorubicin. 134 Recently initiated clinical trials.…”
Section: Update On the Development Of Icd-inducing Chemotherapeuticsmentioning
confidence: 99%
“…Combination therapy of cyclophosphamide with the antibody eliminated residual disease by inducing a secretion phenotype that increased infiltration of macrophages into the bone marrow and enhanced phagocytic activity (Pallasch et al, 2014).…”
Section: Using Detailed Intravital Imaging In a Mouse Model Of Cancermentioning
confidence: 99%